Peran Intelijen Melalui Perumusan Kebijakan Pertahanan Negara dalam Perang Hibrida - Sarjito, Aris (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
Hybrid warfare, with its blend of conventional military tactics, irregular warfare, cyber attacks, and information operations, presents complex challenges to national security. The role of intelligence in understanding, countering, and formulating effective defense policies in hybrid warfare contexts is crucial. This qualitative research study examines the multifaceted role of intelligence in addressing hybrid warfare threats and shaping national defense policies. Utilizing secondary data sources, including government reports, academic publications, and policy analyses, the study employs thematic analysis to explore three key areas: (1) the role of intelligence in understanding and countering hybrid warfare threats; (2) integrating intelligence insights into formulating national defense policies to address hybrid threats; and (3) challenges in employing intelligence-led defense policies in hybrid warfare contexts. Findings highlight the significance of intelligence in providing situational awareness, informing policy decisions, and mitigating risks in hybrid warfare scenarios. The study ends by stressing how important it is for leaders to be able to adapt, for institutions to work together, and for ethical concerns to be taken into account when improving intelligence capabilities and making the best use of them to deal with the changing challenges of hybrid warfare.